Chemical and pharmacological comparison of modern and traditional dosage forms of Joshanda. Issue 6 (19th March 2019) - Parveen, Sajida; Irfan Bukhari, Nadeem; Shehzadi, Naureen; Qamar, Shaista; Ali, Ejaz; Naheed, Surriya; Latif, Abida; Yuchi, Alamgeer; Hussain, Khalid
Abstract: Recently, a traditional remedy ( Joshanda) has been replaced largely by modern ready-to-use dosage forms, which have not been compared to the original remedy. Therefore, the present study aimed to compare a number of modern dosage forms with traditional remedy. Seven brands, 3 batches each, were compared with a Lab-made formulation with reference to analytical (proximate analyses, spectroscopic and chromatographic metabolomes) and pharmacological profiles (anti-inflammatory and antibacterial activities). Chemical and pharmacological differences were found between Lab-made Joshanda and modern dosage forms. Such variations were also found within the brands and batches of modern formulations ( p  < 0.05). The Lab-made Joshanda showed significantly higher pharmacological activities as compared to modern brands ( p  ). The results of the present study indicate that modern dosage forms are unstandardised and less effective than the traditional remedy. Characteristic profiles obtained from Lab-made Joshanda may be used as reference to produce comparable dosage forms. Abstract :